"Caught in the Nets of 'Discipline'": Understanding the Possibilities for Writing Teachers' Resistance to Standardization in Local Policy. Issue 1 (January 2019) - Duarte, Bryan J.; Brewer, Curtis A.
This article contributes to the practice of critical policy analysis by using de Certeau's concept of consumption to analyze how writing teachers resist policies that work to systemize and commodify student writing. Through narratives, we represent the ways teachers tactically and strategically sidestepped the mandated curriculum in an effort to support their sociocultural views of writing. We use a poem built from participant responses to represent discomfort that teachers felt from dominant forms of organization that tried to define writing instruction. These multiple forms of representation extend the practice of critical policy analysis by allowing us to evoke the grind of resistance to local policy.